Paciente femenina de 23 años de edad con anorexia nerviosa - Valverde Anzules, Lindy Tatiana (2019)
Anorexia is currently recognized by the population as a warning sign in which an exaggerated "loss of appetite" can be seen in the patient; However, in some patients they are hungry, in the same way they tend to reject food, because they are afraid of gaining weight, confusing themselves in front of the mirror. The clinical manifestations of anorexia nervosa are multisystemic because there is variation in all parts of the body triggering malnutrition, causing irreversible damage. The dietary prescription for the patient is a complete hyperproteic diet, since it contains foods rich in proteins, in addition to the diet is added a supplement for favorable weight gain. Anorexia nervosa is the most frequent cause in adolescence (women). In the past, anorexia nervosa was known as a disorder of eating behavior.